Serum amyloid A gene expression under acute-phase conditions involves participation of inducible C/EBP-beta and C/EBP-delta and their activation by phosphorylation. - Ray, A (1994)
Serum amyloid A (SAA) is a plasma protein whose synthesis is markedly increased in the liver during the inflammatory process. Previous analysis of SAA promoter function implicated the involvement of the CCAAT/enhancer-binding protein (C/EBP) in controlling this process. In this study, using antibodies against three C/EBP isoforms in DNA-binding and Western blot (immunoblot) assays, we found that in response to inflammatory signals, both C/EBP-delta and C/EBP-beta are induced and that their interactions with the SAA promoter element are necessary for the increased SAA gene expression. Cotransfections of liver cells with an SAA promoter-linked reporter chloramphenicol acetyltransferase gene and murine sarcoma virus-expressed C/EBP-delta or C/EBP-beta confirm such phenomena. The increased transactivating ability in the presence of the cellular phosphatase inhibitors okadaic acid and sodium orthovanadate, coupled with the observation that dephosphorylation severely inhibits the DNA-binding ability in vitro, implicates a role of phosphorylation in the regulation of the activities of the C/EBP-delta isoform. Consistent with these findings, we have detected higher levels of DNA-binding activity of C/EBP-delta prepared from cells treated with phosphatase inhibitors. We also present evidence that C/EBP-delta is a phosphoprotein. These results suggest that C/EBP-delta is regulated by phosphorylation and, in conjunction with C/EBP-beta, is one of the major proteins responsible for the increased transcription of the SAA gene in response to inflammatory stimuli.